Economics of fairness within the food supply chain in context of the EU - Blizkovsky, Petr; Berendes, Vincent (Applied Studies in Agribusiness and Commerce, 2016)
The paper broaches the issue of unfair trading practices (UTPs) at the expense of, economically spoken, weaker actors among the food supply chain in context of the EU. For illustrating the concept of UTPs and delivering a theoretical basis for scrutinizing the term of fairness in respective trading practices the paper suggests the three variables 1) bargaining power, 2) market power/anti competitive practices and 3) unequal gain distribution. Subsequently the article presents selected national food-specific legislative based reactions towards UTPs evolved in context of the three variables. Ultimately the paper presents a qualitatively generated hypothesis which presumes that legislative food-specific measurements focussing on protecting suppliers lead to a beneficial monetary share for farmers, by means of influencing the producer price to a monetarily advantageous extent. The hypothesis was generated unprejudiced in the run-up to the paper. The research design which led to the hypothesis mentioned will be presented.